Visual Outcome after Vitrectomy with Subretinal tPA Injection to Treat Submacular Hemorrhage Secondary to Age-Related Macular Degeneration or Macroaneurysm - Yasmin Ali Said; Evelien Dewilde; Peter Stalmans (Journal of Ophthalmology)
Purpose. To determine the efficacy and safety of 23G transconjunctival sutureless vitrectomy, subretinal injection of tissue plasminogen activator using the EVA Surgical System, and pneumatic displacement with air to treat submacular hemorrhages. Methods. Retrospective analysis of 93 eyes surgically treated for submacular hemorrhage caused by neovascular AMD or retinal macroaneurysms. Main Outcome Measures. Postoperative visual acuity and surgical complications. Results. After surgery, visual acuity improved after 6 weeks but decreased again at the final postoperative visit at 8 months due to progression of the underlying disease. Complications consisted of 2 cases of retinal pigment epithelial tear, 7 vitreous hemorrhages, 4 hyphema, 6 cases of retinal detachment, and 2 subchoroidal hemorrhages during the follow-up period. Conclusions. This study suggests that a surgical approach with 23G vitrectomy, subretinal tPA injection, and pneumatic displacement using air may be an effective procedure for submacular hemorrhage displacement in patients with AMD and retinal macroaneurysms. However, visual outcome is limited by the underlying macular pathology. Larger multicenter randomized controlled studies are warranted to determine the therapeutic effect of this surgical approach.